#TITLE_ALTERNATIVE# - (NIM 10103051), STEFANUS
A row stochastic matrix is a square real matrix which each row sum equals one. Sometimes we need a root of a stochastic matrix that is also stochastic. Qi-Ming He dan Eldon Gunn [2] have obtained the formulas for computing the stochastic roots of stochastic matrices of sizes two by two and three by three. Using the Jordan form of a matrix dan algebraic manipulation, they can compute the stochastic roots for stochastic matrices of size two by two. Whereas for stochastic matrices of size three by three, they make use of the Cayley-Hamilton Theorem. This thesis tries to write down some of the theories they used and also to rewrite the results they arrived at with a different presentation.